Differences between new IFRS and US GAAP lease standards and their effects on publicly listed companies - Karolina Winiarska (Financial Internet Quarterly, 2020)
Leases are quite relevant to a large number of enterprises. Due to the fact that a lease reduces an entity's exposure to risks inherent in asset ownership, it is a widely used method of obtaining access to property, plant and equipment. At the beginning of this article sources of existence of various international accounting standards as well as primary incentives (estimation of unrecognized lease obligations) to change the previous widespread lease standards used by publicly listed companies are mentioned. The IASB and FASB aware of the importance of this issue, put forward new similar accounting solutions. Despite the joint effort, there are some discrepancies between promulgated IFRS 16 and ASC 842. In the article they are divided into three groups of differences (basic, accounting and other lease issues). The main objective of this article is to point out those differences between new lease standards, as well as their distinct effects on the reporting entities' financial statements and crucial financial metrics. In particular, the impact of operating lease capitalization on the Warsaw Stock Exchange entities' assets by sector indices, as well as on EBITDA by industries on the global scale are presented. The article involves research methods such as: analysis of literature, global accounting regulations and financial statements, as well as comparison and deduction methods.
Keywords: G32; M41; M48; 330; Leasing; Accounting; Financial Reporting Standards; GAAP